The Training on the Making of Supplementary Multinutrient Block for Sumba Ongole Cattle in Wunga Village, Haharu District, East Sumba Regency - Marselinus Hambakodu; Mersan M. Yanggu; Andreas Maramba Jara (MITRA: Jurnal Pemberdayaan Masyarakat, 2022)
The livestock farming system of sumba ongole cattle that people in Wunga Village, Haharu District, East Sumba Regency, commonly practice is the extensive system. In this system, sumba ongole cattle are released during the day to graze on natural grazing fields and put back into their pens at night. However, the quality of the pasture during the dry season tends to be very poor, characterized by high crude fiber content and low crude protein content. This condition can cause a nutritional deficiency in the livestock. Therefore, there have been some efforts to meet the nutritional needs of the livestock by providing supplementary feed in the form of a multi-nutrient block (MnB). This community service aims to provide training on how to produce multi-nutrient block as additional supplementation for the sumba ongole cattle, targeted at the Parengu Wunga farmer community (KO MANUNGGA) in Wunga Village, Haharu District, East Sumba Regency as the work partner. The program consisted of several activities, such as lectures, question and answer sessions, discussion, simulation, and practice. These activities were carried out in several stages, namely the survey, the provision of tools and materials, training and mentoring, the feeding of the livestock, and evaluation. The results showed that the livestock farmers in Wunga Village learned about the formulation of a multi-nutrient block, the manufacturing of the multi-nutrient block using local feed ingredients, and the ways to feed the multi-nutrient block to the livestock. It is also revealed that feeding the multi-nutrient block to the sumba ongole cattle can increase their appetite and lead to a high body condition score in the dry season.